Crystal structure of diammonium bis[tris(oxamide dioxime-κ(2) N,N′)nickel(II)] bis[tris(oxalato-κ(2) O,O′)chromate(III)] 6.76-hydrate - Mbiangué, Yves Alain (Acta Crystallogr E Crystallogr Commun, 2020)
The asymmetric unit of the title compound, (NH(4))(2)[Ni(C(2)H(6)N(4)O(2))(3)](2)[Cr(C(2)O(4))(3)](2)·6.76H(2)O, comprises two NH(4) (+) cations, two [Ni(C(2)H(6)N(4)O(2))(3)](2+) cations and two [Cr(C(2)O(4))(3)](3–) anions, as well as eight water molecules of crystallization of which only one is fully occupied. In the cationic and anionic complexes, the central atoms (Ni(II) and Cr(III)) are each surrounded by three bidentate ligands (N-chelating oxamide dioxime and O-chelating oxalate, respectively), resulting in distorted octahedral coordination spheres. In the crystal, O—H⋯O hydrogen bonds between the oxamide dioxime ligands as donor groups and the oxalate ligands as acceptor groups alternately connect the cationic and anionic complexes into infinite pillars extending parallel to [100]. Moreover, N—H⋯O hydrogen bonds between the same ligands connect neighboring pillars, thus delineating channels that accommodate the charge-balancing NH(4) (+) cations as well as the water molecules of crystallization. Although the H atoms could not be localized for these two species, the corresponding N⋯O and O⋯O distances indicate hydrogen bonds of medium strength.